Narrative Shelter for Young People with Childhood Experiences of Intimate Partner Violence: A Concept for Creating Opportunities for Storytelling, Storylistening, and Resilience - Nyirinkwaya, Serge; Jenney, Angelique (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2023)
Objectives: Childhood experiences of intimate partner violence (CEIPV) remain a significant public health issue affecting millions of young people (YP) globally. Although CEIPV has been researched for decades, YP’s voices are often left unheard, their stories relegated to mere research data. Their CEIPV are usually told through adult proxy accounts rather than by YP themselves. Additionally, research shows that YP have limited opportunities to influence domestic violence policies and practices. This theoretical paper proposes a new YP engagement model for CEIPV research and practice.Methods: The model is based on a review of relevant literature, including lessons from the women’s shelter movement, child rights, narrative practice, trauma and violence-informed approaches, and selected case studies.Results: The Narrative Shelter Model integrates storytelling and storylistening to create a safe space for YP with CEIPV to exercise their voice and choice, and share their stories in a non-retraumatizing way. Moreover, the model invites the storylistener(s) to connect with YP’s stories to influence decision-making.Conclusion: The Narrative Shelter Model elicits a path towards creating safe and inclusive spaces for YP with CEIPV to share their stories and be heard as agents of social change. It aims not only to promote their voices but also to empower them to become young advocates and peer supporters in responding to IPV, thereby strengthening their resilience and recovery. The use of this model within domestic violence agencies can continue to position YP as experts in their own lives and pivotal agents in shaping knowledge and effective interventions.